2018
DOI: 10.1016/j.theriogenology.2017.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Seminal plasma and sperm proteome of ring-tailed coatis (Nasua nasua, Linnaeus, 1766)

Abstract: Ring-tailed coati is listed as a species of least concern in the International Union for Conservation of Nature (IUCN) Red List, however, there has been a sharp decline in their population. The present study was conducted to evaluate the major proteins of both seminal plasma and sperm in ring-tailed coatis. Semen sample was collected from three adult coatis and evaluated for their morphological characteristics. Further, the sample was centrifuged to separate spermatozoa from seminal plasma, and then stored in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…Here, it should be noted that some proteins are simultaneously presented in sperm and seminal plasma. In previous studies, the similar phenomenon was also observed 24 26 . Some major proteins in sheep seminal plasma, such as ram seminal vesicle protein 14 and bodhesin 2, also appeared in plasma membrane 25 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Here, it should be noted that some proteins are simultaneously presented in sperm and seminal plasma. In previous studies, the similar phenomenon was also observed 24 26 . Some major proteins in sheep seminal plasma, such as ram seminal vesicle protein 14 and bodhesin 2, also appeared in plasma membrane 25 .…”
Section: Discussionsupporting
confidence: 83%
“…Some major proteins in sheep seminal plasma, such as ram seminal vesicle protein 14 and bodhesin 2, also appeared in plasma membrane 25 . In ring-tailed coatis, some proteins identified in sperm also appeared in their corresponding seminal plasma 24 . Furthermore, lots of proteins identified in human seminal plasma (70%) are also a part of sperm proteome 26 .…”
Section: Discussionmentioning
confidence: 99%
“…And both cleavage rates and blastocyst growth were similar after ejaculated sperm were incubated with heparin, BSP-1+heparin or BSP-1. With epididymal sperm, the best results or capacitation and blastocyst growth were obtained with BSP-1, when compared to heparin and heparin+BSP-1 (Rodriguez- Villamil et al, 2018; Federal University of Ceara, Fortaleza, Brazil; unpublished data). Thus, BSP-1 is a potent capacitating factor for bovine sperm and it increases fertilization rates, with no dependence on heparin.…”
Section: Proteins Involved In Sperm Capacitation Acrosome Reaction Amentioning
confidence: 99%
“…High levels of clusterin are associated with advanced physiopathological states, such as kidney diseases, neurodegenerative disorders, artheriosclerosis, heart attack and cancer ( Wehrli et al ., 2001 ; Trougakos et al ., 2002 ; Pucci et al ., 2004 ; Calero et al ., 2005 ). We have characterized the seminal plasma proteome of several domestic and wild species, including bulls ( Moura et al ., 2007a ; Rego et al ., 2014 , 2016 ; Menezes et al ., 2017 ), rams ( Souza et al ., 2012 ), boars ( González-Cadavid et al ., 2014 ), peccaries ( Santos et al ., 2014 ), dogs ( Aquino-Cortez et al ., 2017 ) and coatis ( Silva et al ., 2018 ), among others. Clusterin is present in the semen of all these species, in moderate to high concentrations.…”
Section: Seminal Plasma Proteinsmentioning
confidence: 99%
“…The first evidence of GST activity in mammalian sperm dates back to 1978 in murine species (Mukhtar et al, 1978), and the first report confirming the presence of the Pi class of GSTs (GSTP1) was published in 1998 in goat sperm . Since then, several proteomic profiling studies have identified GSTP1 in the sperm cells of a wide range of mammalian species, including humans (Wang et al, 2013), mice (Vicens et al, 2017), pigs (Pérez-Patino et al, 2019), cattle (Peddinti et al, 2008), and coatis (Rodrigues-Silva et al, 2018). In somatic cells, the main well-defined function of GSTP1 is cell signaling regulation via inhibition of the c-Jun N-terminal kinase (JNK)-C-Jun pathway (Adler et al, 1999;Wang et al, 2001;Turella et al, 2005).…”
Section: Introductionmentioning
confidence: 99%